Short- and Long-Term Outcomes of Prenatally Diagnosed Dandy-Walker Malformation, Vermian Hypoplasia, and Blake Pouch Cyst. (October 2021) - Venkatesan, Charu; Kline- Fath, Beth; Horn, Paul S.; Poisson, Kelsey E.; Hopkin, Rob; Nagaraj, Usha D.
Dandy-Walker continuum, which includes Dandy-Walker malformation, vermian hypoplasia, and Blake pouch cyst, is among the most commonly diagnosed posterior fossa malformation by fetal magnetic resonance imaging (MRI). The objective of our retrospective study was to evaluate fetal and postnatal MRI scan and clinical outcomes. Seventy-two patients were identified; 40 patients had postnatal imaging and follow-up (7 Dandy-Walker malformation, 26 vermian hypoplasia, and 7 Blake pouch cyst). Although all patients with Dandy-Walker malformation required ventriculoperitoneal shunts and 66% were intubated at birth, none required tracheostomy tube and 2 of 5 surviving children had no neurologic deficits. Vermian hypoplasia was strongly associated with genetic conditions and cardiac malformations; odds of not ambulating normally were 12 times greater if a syndrome or injury was present. Echocardiogram and genetic screening are recommended with vermian hypoplasia. There is a risk for epilepsy in both Dandy-Walker malformation and vermian hypoplasia. Blake pouch cyst can be complicated by hydrocephalus, but outcome is favorable.